2012
DOI: 10.1371/journal.pone.0049013
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+ Influence on Calmodulin Unfolding Pathway: A Steered Molecular Dynamics Simulation Study

Abstract: The force-induced unfolding of calmodulin (CaM) was investigated at atomistic details with steered molecular dynamics. The two isolated CaM domains as well as the full-length CaM were simulated in N-C-terminal pulling scheme, and the isolated N-lobe of CaM was studied specially in two other pulling schemes to test the effect of pulling direction and compare with relevant experiments. Both Ca2+-loaded CaM and Ca2+-free CaM were considered in order to define the Ca2+ influence to the CaM unfolding. The results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…This observation was similar to that of pearl oyster and freshwater mussel CaMs (Li et al, 2005;Ren et al, 2013). The binding of Ca 2+ ions could induce a conformational change of CaM to be compact, while apo-CaM may be in a less compact form, resulting in the different electrophoretic mobility (Zhang and Lou, 2012). This result was also supported by CD experiment, in that Ca 2+ ions increased α-helical content of rPmCaM when compared to that of the apoprotein.…”
Section: Discussionsupporting
confidence: 81%
“…This observation was similar to that of pearl oyster and freshwater mussel CaMs (Li et al, 2005;Ren et al, 2013). The binding of Ca 2+ ions could induce a conformational change of CaM to be compact, while apo-CaM may be in a less compact form, resulting in the different electrophoretic mobility (Zhang and Lou, 2012). This result was also supported by CD experiment, in that Ca 2+ ions increased α-helical content of rPmCaM when compared to that of the apoprotein.…”
Section: Discussionsupporting
confidence: 81%
“…We therefore expect that removal of Ca 2+ from EF3 or EF-1 would disrupt the structural integrity of the CaM, hence DNA binding [17]. Moreover, previous molecular dynamics simulation indicated that removal of even a single Ca 2+ ion could induce unfolding of CaM, and hence the overall structure adopts a closed conformation [2]. Therefore, we expect that mutation of even a single EF-hand motif is sufficient to change the conformation of CaM, and when done in the C-terminal domain would abolish structural integrity of the C-terminal domain and thus the DNA interactions [17].…”
Section: Discussionmentioning
confidence: 97%
“…CaM plays essential role in Ca 2+ signaling, regulating numerous intracellular processes such as cell motility, growth, proliferation, and apoptosis . CaM binds Ca 2+ ions using its helix‐loop‐helix (EF‐hand) structural motif, and this motif generally undergoes large conformational changes upon Ca 2+ binding . In the Ca 2+ ‐loaded form, the CaM adopts stable state, and each EF‐hand opens so that its two alpha helices become perpendicular to each other.…”
mentioning
confidence: 99%
“…Several studies proposed higher stability for the N-domain in both apo-and CaCaM attributing the transitions with higher heat capacities to the N-lobe. 4,5,32 In contrast, other authors suggested a reverse order of stability in apo-and CaCaM 2,3 F I G U R E 5 Heat stability of human and Pf CaM. Thermal stability was studied by DSC in standard assay buffer.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…The C-terminal domain bears higher affinity Ca 2+ -binding sites, so it is expected to possess higher stability in Ca 2+saturated CaM (CaCaM) as it was proposed in studies using experimental or computational approaches. 2,3 In contrast, higher stability for the N-terminal domain (N-domain) in both apo and holo CaM forms was suggested based on thermal melting profiles observed with differential scanning calorimetry. 4,5 Ca 2+ -binding to CaM results in a global conformational change involving rearrangement of the helices as well as additional helix formation.…”
Section: Introductionmentioning
confidence: 99%